EFEK ANTIDIARE EKSTRAK ETANOL DAUN KEJI BELING (STROBILANTHES CRISPUS) TERHADAP MENCIT (MUS MUSCULUS) JANTAN YANG DIINDUKSI CASTOR OIL - Arum Suproborini; M. Soeprijadi Djoko Laksana; Puri Ratna Kartini; Dentha Lorenza Prastyana Putri (Universitas Lambung Mangkurat, 2022)
Poor sanitation and environmental hygiene are factors that cause the high incidence of diarrhea in Indonesian children. The use of traditional medicines derived from plants is increasingly in demand by the public. The Strobilanthes crispus plant is very potential as a natural antidiarrheal drug because of its phytochemical content, namely tannins, silicates, and catechins which are natural compounds of the flavonoid group. The purpose of this study was to determine the effectiveness of Strobilanthes crispus extract as an antidiarrheal. This study uses an experimental laboratory method. Group I. 100 mg/Kg BW, group II. 200 mg/Kg BW, group III. 400 mg/Kg BW, group IV. 800 mg/Kg BW, group V. positive control (+) loperamide 2 mg, and group VI. negative control (-) distilled water. Induction of diarrhea with castor oil. The results of the positive control statistical test with the negative control showed that the p value <0.05 was significant, there was a difference in the time of diarrhea in mice that were given loperamide and mice that were not given loperamide. The results of the statistical test of negative control and the treatment of giving kejibeling extract showed that the p value <0.05 there was a difference in the time of diarrhea in mice that were given kejibeling extract and those that were not given kejibeling extract. The results of statistical tests on the treatment of Kejibeling extract with positive control showed that the p value> 0.05 had no effect on the time of diarrhea. This indicated that the kejibeling extract had the same effect as the positive control (loperamide). Kejibeling can be used as an alternative to loperamide.